Persistent expression of NLRP3 in spinal microglia promotes development of lumbar disc degeneration - Wang, Peng; Zhang, Jing (Frontiers in Immunology, 2022)
Activated microglia play a critical role in the development of lumbar disc degeneration (LDD), which is a severe disease that causes neuropathic pain in affected people. Interleukin 1β (IL-1β) is a proinflammatory cytokine produced and secreted by activated microglia to induce the inflammation and the subsequent degradation of the disease discs. Recent findings suggest that activation of IL-1β in cells usually requires the involvement of NACHT, LRR and PYD domains-containing protein 3 (NLRP3)-induced formation of inflammasome. However, the importance of NLRP3 in spinal microglia in LDD is not known and thus addressed in the current study. Here, we found that NLRP3 was exclusively expressed in microglia in the spinal discs. NLRP3 levels in microglia strongly correlated with the pain score of the LDD patients, and modestly correlated with the Thompson classification of the degeneration level of the patients. Persistent NLRP3 expression in microglia increased both their phagocytosis potential and production of proinflammatory cytokines, while NLRP3-depleted microglia decreased both their phagocytosis potential and production of proinflammatory cytokines. In a mouse model for LDD, persistent NLRP3 activation in microglia significantly increased the severity of LDD and LDD-associated neuropathic pain, while specific depletion of NLRP3 in microglia significantly attenuated the severity of LDD and reduced the LDD-associated neuropathic pain. Together, our data suggest that persistent activation of NLRP3 in spinal microglia promotes development of LDD, while suppression of NLRP3 in microglia could be a promising strategy for LDD therapy.